Clothing Pressure Gradient for Comfortable Pantyhose (Journal of Fiber Bioengineering and Informatics, 2023)
Our aim is to develop a pantyhose that fit without being too tight and to reduce muscle fatigue. This study was conducted with 17 Japanese women who wore two types of pantyhose with a structural difference in the panty part. When wearing pantyhose with a clothing pressure that gradually increased from 2.9 hPa in the waist to 11.0 hPa in the foot, participants reported a nearly perfect pressure sensation using a ratio scale. Thus, pantyhose with an optimized pressure sensation can be created according to the clothing pressure gradient rule. When participants wore pantyhose, EMG changes in the lower leg significantly restricted muscle activity when compared to that in the barefoot condition, that was clarified the local distribution of pressure intensity determines the intensity of muscle activity.
Keywords: Japanese Women; Pantyhose; Clothing Pressure; Pressure Sensation; Electromyogram